Keeping Strategy on Track - Published by Harvard Business School (Boston Harvard Business Press, 2008)
"Few management topics generate as much discussion - and disagreement - as strategy. Explore the key issues for yourself through this collection of the most popular Harvard Business Review cases on the topic: Do you really need to take your company global? If so, how and when?: Should you grow from the core - or expand into new markets?: Should you make that next acquisition - or are you "growing for broke?": and How can you provide incentives for collaboration across teams?"--Jacket.
Harvard Business Reviews, Case Studies
Keywords: Strategic Planning -- Case Studies -- Management -- Case Studies -- Management